Camylofin dihydrochloride injection: a drug monograph review - Mayadeo, Niranjan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Camylofin dihydrochloride is an anti-spasmodic drug available in India and other Latin American and African countries, for the treatment of abdominal colic and for acceleration of labor. Although, the drug has been in use for over six decades, with multiple citations in academic text books of repute, treatment protocols, and multiple research publications, there is no consolidated published information on the pharmacology and clinical details of camylofin. This drug statement/monograph is an attempt to collate and present scientific information that will come in handy to practicing obstetricians and gynaecologists, as well as other primary care physicians, when treating cases of abdominal colic or managing prolonged labor. Approved clinical indications, clinical pharmacology, dosage, contraindications, precautions, drug interactions, adverse effects, overdose and clinical evidence in different indications are covered herein.